The multiplicity of religions and the realism-antirealism debate in religion (in Polish) (Diametros, 2011)
In this paper I first briefly outline the difficulty of maintaining a realistic interpretation of religious discourse in the context of religious pluralism. Then I present two attempts to reconcile religious realism and pluralism. The first is John Hick’s proposal, the second the 'internalist pluralism' developed by Victoria Harrison on the basis of Putnam's internal realism (and in opposition to Hick’s conception). I point out the weaknesses of these theories. Finally, I outline my own proposal, based on a slightly different interpretation of internal realism than Harrison’s internalist pluralism, namely by using the pragmatic aspects of Putnam's thought. He argues that pragmatic-realistic pluralism avoids the weaknesses of Hick’s and Harrison’s conceptions while at the same time sharing their strengths.